The unmet needs of family caregivers in the management of childhood community-acquired pneumonia in Indonesia: a qualitative study - Nyimas Heny Purwati; Yeni Rustina; Bambang Supriyatno (Paediatrica Indonesiana, 2022)
Background Childhood community-acquired pneumonia (CAP) is one of the leading causes of morbidity and mortality in children under five years of age. Objective To explore the unmet needs of family caregivers of children with community-acquired pneumonia. Methods A qualitative study using in-depth interviews was conducted at one referral hospital located in Jakarta, Indonesia. Convenience sampling was used to select participants. Data were analyzed using qualitative content analysis. Results Ten family caregivers participated in our study. The results of this research are shown in five main themes: (1) the burden of persistent symptoms; (2) exposure to cigarette smoke at home; (3) home remedies as initial treatment; (4) fulfilling the children’s nutritional needs; and (5) health promotion needs. The care of children with CAP involves more than antibiotic treatment and vaccines. Conclusion This study found several unmeet needs of family caregivers in caring for children with CAP, particulary pertaining to health promotion and the fulfilment of nutritional needs.